An Assessment of Third‐Party Reporting of Close Ties to Measure Sensitive Behaviors: The Confidante Method to Measure Abortion Incidence in Ethiopia and Uganda. Issue 4 (11th November 2021) - Giorgio, Margaret; Sully, Elizabeth; Chiu, Doris W.
Abstract: Indirect estimation techniques are important tools for measuring sensitive and stigmatized behaviors. This includes third‐party reporting methods, which have become increasingly common in the field of abortion measurement, where direct survey approaches notoriously lead to underreporting. This paper provides the first in‐depth assessment of one of the most widely used of these techniques in the field of abortion measurement: the confidante method. We outline six key assumptions behind the confidante method and describe how violations of these assumptions can bias resulting estimates. Using data from modules added to the performance monitoring for action surveys in Uganda and Ethiopia in 2018, we compute one‐year abortion incidence estimates using the confidante method. We also perform a validation check, using the method to estimate intrauterine device /implant use. Our results revealed implementation problems in both settings. Several of the method's foundational assumptions were violated, and efforts to adjust for these violations either failed or only partially addressed the resulting bias. Our validation check also failed, resulting in a gross overestimate of intrauterine device/implant use. These results have implications more broadly for the potential biases that can be introduced in using third‐party reporting of close ties to measure other sensitive or stigmatized behaviors.